Relationship between risk aversion, risky investment intention, investment choices Impact of personality traits and emotion - Aren, Selim; Nayman Hamamci, Hatice (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose This paper aims to examine the effects of subjective and financial literacy, big five personality traits and emotions (fear, anger, hope and sadness) on risk aversion, risky investment intention and investment choices were investigated. Interactions of these three variables (risk aversion, risky investment intention and investment choices) were also examined. Design/methodology/approach For this purpose, in January-February 2019, collected data on 446 subjects from Turkey using the internet (341) and face-to-face (105) survey instruments. The authors exploited IBM SPSS Statistics for analysis. ANOVA, t-test and discriminant analysis were performed. Findings As a result of the analyzes, two personality traits (neuroticism and openness) and two emotions (fear and sadness) were determined as predictors of risk aversion. For risky investment intention, risk aversion, two personality traits (neuroticism and openness) and one of the same and other one different two emotions (fear and anger) were found. Originality/value Investment choices can be estimated by objective financial literature, risk aversion and risky investment intention. In addition, individuals' risk averse or risk taking characteristics differ according to their level of sadness with agreeableness, conscientiousness and neuroticism personality traits. Similarly, have a risky investment intention or have not risky investment intention also differs according to sadness emotions with conscientiousness and openness. Finally, the choice of stocks or bank deposits varies according to subjective financial literacy and extraversion personality trait.
Keywords: Risk aversion; Emotions; Financial literacy; Big five; Investment choices; Risky investment intention; BIG 5; INFORMATION ACQUISITION; DECISION-MAKING; ATTITUDES; FEAR; BEHAVIOR; DOMAIN; ANGER; DETERMINANTS; PREFERENCES; Computer Science